Nursing of a patient with nerve-root type cervical spondylosis treated by acupoint application (穴位贴敷治疗神经根型颈椎病1例的护理体会) - MIAO Yuxin (苗玉鑫); ZHAO Dongfang (赵东方); QI Jiao (祁姣); TANG Ling (唐玲); SUN Yanrong (孙艳荣) (中西医结合护理)
This paper summarized the nursing experience of a patient with nerve-root type cervical spondylosis treated by acupoint application therapy, including clinical observation, nursing assessment and operation methods of acupoint application. The Chinese herbal medicine acupoint application is effective to relieve the symptoms of nerve-root type cervical spondylosis, and it has advantages of simple operation, short-term operation period, obvious curative effect, fewer side effects, low cost and higher patient acceptance. (本文总结穴位贴敷疗法干预1例神经根型颈椎病患者的护理经验, 包括临床症状观察、护理评估、穴位贴敷操作方法等。中药穴位贴敷疗法能有效改善患者症状, 且操作简单、效果显著、不良反应少、价格低廉, 易被患者接受。)